Analysis Of The Income And Cost Structure Of Footwear Msmes In Pagelaran Village - Hidayah, Ulul; Anggelina Delviana Klau; Eka Wirajuang Daurrohmah (Jurnal Ilmiah Ekonomi Dan Bisnis, 2025)
Village economic development can be achieved by paying attention to local potential. Pagelaran Village has local potential in the field of footwear MSME development. In the footwear sector, which is the center of village economic growth, it is necessary to identify the income and cost structure of footwear MSMEs and analyze the factors that influence the income level of footwear MSMEs in Pagelaran Village. The analysis used to answer the objectives of this research is descriptive analysis and multiple linear regression analysis. Data was obtained from interviews of perpetrators with footwear businesses determined using the proportional random sampling method. This research shows differences in business expenses and income structure based on the target market. The amount spent on raw materials, the number of machines and the number of workers owned by a Footwear MSME significantly affect the income of Footwear MSMEs in Pagelaran Village. Meanwhile, the business length does not affect Footwear MSMEs' income in Pagelaran Village.